Isolation and Identification of the Plant Growth-Promoting Bacterium Pseudomonas fluorescens by 16S rRNA Sequence Analysis Its Efficacy as a Bioinoculator - Naseer Jawad Kadhim; Jawad Abdul Kadhim Kamal (Research in Ecology, 2025)
The isolation of bacteria from the rhizosphere soil of different plants and locations in Diwaniyah Governorate and their diagnosis by two methods. Isolation and routine molecular diagnosis revealed ten bacterial isolates with the attributes of P. fluorescens out of fifteen local isolates that are represented by the following codes and sequences (P.f9, P.f8, P.f6, P.f5, P.f4, P.f2, P.f1, P.f14, P.f13, P.f11). Results also confirmed the diagnosis of bacterial isolates by biochemical and molecular tests using a specialized primer to amplify the bp698 region of the 16S ribosomal RNA gene, approved by Macrogen/Korea. The test efficiency in dissolving solid phosphate by P. fluorescens bacteria showed that the most effective is the (P.f1) isolate, giving the highest score effectiveness in mineral phosphate dissolution by the diameter of the clear zone around the colony, which was effective in phosphate dissolution up to 6.95 mm. The efficiency of the Nitrogen Fixation Test showed that the isolate (P.f5) scored the highest nitrogen-fixing efficiency amount with a value of 6.81 mg L–1. The quantitative amount of the hormone for each of Auxins, Cytokinins, and Gibberellins was assayed; the results with isolate (P.f1) for IAA (Auxins) gave a concentration up to 28.6 µg ml–1, which was the most, while the production of GA3 by isolate (P.f1) gave the maximum value of 36.7 µg ml–1, and for synthesis of the hormone of Cytokinins represented by isolate (P.f2), the highest value in the production of Cytokinins hormone was recorded at 26.3 µg ml–1.